Wellness culture : how the wellness movement has been used to empower, profit and misinform - Baker, Stephanie Alice (SocietyNow., 2022)
Wellness has become synonymous with yoga, meditation, and other forms of self-care. Over the past 60 years, what began as an alternative to mainstream medicine has coalesced with consumer culture and has been commercialised to such an extent that the term is now synonymous with an industry of exclusive products and services. This book traces the emergence of wellness culture as a countercultural movement to a trillion-dollar industry, examining the social, economic and political conditions that enabled wellness to assume mainstream cultural significance. It explores the role of the internet in making wellness more accessible to consumers, while simultaneously questioning who wields influence in these digital spaces. A must read for anyone interested in learning about wellness and its online penetration, Wellness Culture offers an in-depth yet accessible examination of how wellness has been weaponised during the COVID-19 pandemic to spread medical misinformation, conspiratorial thinking and political extremism.